Edukasi Penguatan E-modul Kepedulian Lingkungan Pada Siswa Sekolah Dasar Negeri 2 Dewantara Aceh Utara - Syifa Saputra; Irwansyah; Ilham Akbar; Husnul Mannan (LPPI UMN AL WASHLIYAH, 2026)
Global environmental issues have become an important concern that must be addressed from an early stage through education. As the foundation of formal education, elementary schools play a significant role in developing students’ character and environmental awareness. This study aimed to develop an interactive E-Module based on ecosystem profiles for the Science and Social Studies (IPAS) subject, particularly on waste management material for fourth-grade students at SD Negeri 2 Dewantara. The data collection methods employed in this study included interviews, observations, and questionnaires. The research instrument used for data collection was a questionnaire. The data obtained were analyzed using a descriptive qualitative approach. The findings revealed an improvement of 60% in students’ competency outcomes related to waste management material. Therefore, it can be concluded that the developed E-Module was effective in supporting the learning process in the IPAS subject.